Protokol New Normal Order Pasca Pandemi COVID-19 dalam Pengembangan Kampoeng Boenga Grangsil Berbasis Masyarakat - Respati Wikantiyoso; Diyah Sukanti Cahyaningsih; Aditya Galih Sulaksono; Sri Widayati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
The tourism development sector in Indonesia is overgrowing. During the COVID-19 pandemic, it was the sector most affected economically. The COVID1-9 pandemic has changed the "normal" conditions in all life sectors, including tourism sector activities. The uncertainty over the end of the COVID-19 pandemic requires us to adapt to the new conditions, the new prerequisites (social and physical distancing), and the new order (physical, social, and health) preparing the new normal order protocol. The recovery of tourism sector activities must be aware of the emergence of new clusters in tourist destinations. The purpose of the discussion in this paper is to produce a new normal order protocol after the COVID-19 pandemic for the development of sustainable community-based rural tourism destinations. The efforts that prepare are the new normal order after COVID-19, by taking into account: (1) Mitigation of tourism "disasters" due to COVID-19; prevent new clusters in tourist villages/villages (2) Compilation of health protocols for tourist destinations during the COVID-19 pandemic era; (3) Strengthening information on destination environmental health; (4) Strengthening the Destination Management Organization (DMO) especially for the management of the COVID-19 tourism village protocol; and (5) Increasing stakeholder participation towards a new normal order.DOI: https://doi.org/10.26905/abdimas.v5i3.4803